Features of managing the creative development of the socio-economic system in the conditions of influence of COVID-19 pandemic - Kopytko, Marta; Zaverbnyj, Andrij; Diachuk, Iryna; Nikonenko, Uliana; Khalina, Olena (Creativity Studies, 2023)
The main purpose of the study is to model the process of managing the creative development of the socio-economic system in the conditions of influence of COVID-19 pandemic. For this, we have applied the methodology of functional modeling and graphical display, which includes the possibility of structural analysis and serves as effective information technology for any control system. Socio-economic systems are a large number of complex organizational structures with a large number of management processes. The largest of these are companies and organizations with appropriate personnel, on which it depends on where the company will move. It is impossible to compete without creative development. For an illustrative example, we used the current socioeconomic system in the form of a company, in which creativity and creative development play an important role. As a result, we reflected how, through a convenient and easy-to-use model, it is possible to form clear steps and stages that would informatively reflect creative development for the socio-economic system (company).